Dialogias no cronotopo pandêmico: sentidos emergentes em narrativas sobre o ensino-aprendizagem em uma escola pública do Piauí - Queiroz, Marília Mesquita (Universidade Federal de São Carlos, 2025)
In the chronotope of the covid-19 pandemic, institutions across various spheres of human activity were compelled to self-organize in response to the unforeseen circumstances faced during this period. In the field of education, these rearrangements have been documented through diverse lenses, contributing to the understanding of how school systems adapted in different contexts. This study, grounded in categorical narrative research (Breton, 2023; Clandinin et al., 2016; Paiva, 2019; Reis, 2023), analyzes reports from the book “Sozinho na minha torre”: representações discentes sobre o ensino remoto no Piauí, written in 2023 by high school students from a federal institution in Piauí. The objective is to examine the meanings these students attribute to remote teaching and learning, particularly in relation to the English language. Based on the understanding of education as a complex phenomenon (Davis and Sumara, 2006; Freire, 2011; Freire, 2013; Morin, 1995; Morin, 2021), we reflect on the multidimensionality inherent to the school system and on the interactive and inter-retroactive relationships between learning and teaching. Analytical categories and concepts include dialogism, meaning (Bakhtin, 2017 [1979]; Volóchinov, 2018; Vygotsky, 2007), chronotope (Bakhtin, 2018 [1975]; Bemong, 2015), autonomy (Morin, 2021; Paiva, 2005), and emotion (Aragão, 2008; 2011; Maturana, 2001; Maturana e Varela, 1998), which emerge consistently in the students’ narratives. Considering the shift from physical to virtual learning environments, the study also addresses digital literacy, with support from Coscarelli (2016), Lankshear and Knobel (2006), Rojo and Moura (2019), Santaella (2010), Soares (2002, 2009), and Street (2013, 2014). Besides serving as a historical record of the educational experience during the pandemic, the research highlights the value of amplifying student voices, reinforcing their legitimacy and capacity to inform systemic improvements. As an applied study, it further explores non-linearity, complexity, and possibilities in language teaching and learning, building on Larsen-Freeman and Cameron (2008) and Paiva (2010, 2014), among others. The findings indicate that remote teaching was often perceived as having limited relevance for learning, prompting some students to engage in autonomous learning practices, both generally and specifically in the English subject. The home, as the new learning space, was reinterpreted with varied meanings: confinement, confusion, leisure, overload, and overcrowding. Emotional and psychological impacts – such as fear, anxiety, and difficulties in concentration and social interaction upon returning to in-person classes – were also frequently reported.

Dans le chronotope de la pandémie de la covid-19, les institutions des différentes sphères de l'activité humaine ont été confrontées à l’impératif de s’auto-organiser face à la situation imprévue à laquelle l’humanité s’est heurtée pendant cette période. Dans le domaine de l’éducation, ces réajustements ont été représentés sous différents angles, contribuant à la compréhension de la manière dont, dans divers contextes, les systèmes scolaires se sont auto-organisés. À partir d’une recherche narrative catégorielle (Breton, 2023 ; Clandinin et al., 2016; Paiva, 2019; Reis, 2023), ayant pour objet d’étude les récits du livre Sozinho na minha torre: représentations d’élèves sur l’enseignement à distance au Piauí, produits en 2023 par des lycéens d’un établissement fédéral situé au Piauí, nous proposons comme objectif général de ce travail d’analyser les significations attribuées par ces élèves à l’enseignement et à l’apprentissage en mode à distance, en particulier en ce qui concerne la discipline de langue anglaise. En nous fondant sur la conception de l’éducation comme phénomène complexe (Davis et Sumara, 2006; Freire, 2011; Freire, 2013; Morin, 1995; Morin, 2021), nous réfléchissons à la multidimensionnalité du système scolaire ainsi qu’aux relations interactives et inter-rétroactives entre apprendre et enseigner. Des concepts et catégories tels que dialogisme, signification (Bakhtin, 2017 [1979]; Volóchinov, 2018 [1929]; Vygotski, 2007), chronotope (Bakhtin, 2018 [1975]; Bemong, 2015), autonomie (Morin, 2021; Paiva, 2005) et émotion (Aragão, 2008; 2011; Maturana, 2001; Maturana et Varela, 1998) ont été essentiels pour orienter les analyses, car ils émergent fortement dans les énoncés étudiés. En raison de la migration de l’espace habituel d’apprentissage vers l’environnement virtuel, nous abordons également la question de la littératie numérique, en nous appuyant sur des auteurs tels que Coscarelli (2016), Lankshear et Knobel (2006), Rojo et Moura (2019), Santaella (2010), Soares (2002 ; 2009) et Street (2013; 2014). En plus de constituer un registre historique du système scolaire étudié durant la pandémie, ce travail se justifie par la création d’opportunités permettant que les voix des élèves soient entendues de manière plus ample, renforçant leur légitimité et leur potentiel à provoquer des transformations et des améliorations. De nature appliquée, cette étude apporte également des réflexions sur la non-linéarité, les complexités et les possibilités liées à l’enseignement et à l’apprentissage des langues, en s’appuyant sur Larsen-Freeman et Cameron (2008) et Paiva (2010; 2014), entre autres auteurs. Les analyses montrent que les significations attribuées à l’enseignement à distance tendent à le considérer comme peu pertinent pour l’apprentissage, poussant certains sujets à adopter des démarches autonomes dans la recherche de connaissances, tant de manière générale que concernant spécifiquement la discipline d’anglais. Liée au nouvel espace d’apprentissage, la maison a également été re-signifiée, recevant des sens tels que prison, désordre, loisir, surcharge, surpopulation. Des questions émotionnelles et psychologiques, telles que la peur, l’anxiété, les difficultés de concentration et d’interaction lors du retour en présentiel ont été signalées par les élèves comme des impacts de l’enseignement à distance.
Dialogisms in the pandemic chronotope: emerging meanings in narratives on teaching and learning in a public school in Piauí
Dialogismes dans le chronotope pandémique: sens émergents dans des récits sur l’enseignement-apprentissage dans une école publique du Piauí
Keywords: Cronotopo pandêmico; Ensino-aprendizagem de inglês; Dialogismo; Sentidos; Emoções; Pandemic chronotope; English language teaching and learning; Dialogism; Meanings; Emotions; Chronotope pandémique; Enseignement-apprentissage de l’anglais; Dialogisme; Significations; Émotions; LINGUISTICA, LETRAS E ARTES::LINGUISTICA